2018
DOI: 10.1111/cas.13854
|View full text |Cite
|
Sign up to set email alerts
|

Development of a T‐cell receptor multimer with high avidity for detecting a naturally presented tumor‐associated antigen on osteosarcoma cells

Abstract: For efficacy of peptide vaccination immunotherapy for patients with cancer, endogenous expression of the target peptide/human leukocyte antigen (HLA) on cancer cells is required. However, it is difficult to evaluate the expression status of a peptide/HLA complex because of the lack of a soluble T‐cell receptor (TCR) that reacts with tumor‐associated antigen (TAA) with high avidity. In the present study, we developed two soluble TCR‐multimers that were each directed to TAA, survivin‐2B (SVN‐2B) and PBF in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…To further study the immune response of T cells to neoantigens, we collected validated T-cell receptor-β (TCRβ) complementarity-determining region 3 (CDR3) sequences specific for tumor neoantigens (class I or II) and firstly constructed TCRβ-CDR3 sequence libraries. Eventually, we unified retrieved information and each entry was provided with cancer type, gene name, neoantigen sequence, CDR3 sequence, variable region of TCR (TRBV), diversity region of TCR (TRBD), and joining region of TCR (TRBJ) ( 36 ), as well as the reference links, if available in literatures.…”
Section: Methodsmentioning
confidence: 99%
“…To further study the immune response of T cells to neoantigens, we collected validated T-cell receptor-β (TCRβ) complementarity-determining region 3 (CDR3) sequences specific for tumor neoantigens (class I or II) and firstly constructed TCRβ-CDR3 sequence libraries. Eventually, we unified retrieved information and each entry was provided with cancer type, gene name, neoantigen sequence, CDR3 sequence, variable region of TCR (TRBV), diversity region of TCR (TRBD), and joining region of TCR (TRBJ) ( 36 ), as well as the reference links, if available in literatures.…”
Section: Methodsmentioning
confidence: 99%
“…Target cell identification may be achieved through different approaches. One possibility is to stain tissue cells with fluorescent TCR multimers ( 89 ). We had co-cultured TCR hybridomas generated from lesional psoriatic CD8 + T cell clones with skin-specific cell types, which corresponded to the actual site of the immune response.…”
Section: Identification Of Tcr Epitopes In Hla-associated Autoimmune ...mentioning
confidence: 99%
“…PBF A24.2 peptides are determined to activate CTLs from HLA-A24-positive patients with OS and therefore trigger immunity to eliminate tumor cells (152). A PBF TCRmultimer has been successfully created to recognize the naturally presented PBF peptide on HLA-A24 + PBF + OS cells (153). Although data about the usage of PBF-modified T cells in treating OS are not available, studies of this issue are critical, as suggested by the encouraging results with PBF's role in oncogenicity and immunogenicity.…”
Section: Tcr T Therapymentioning
confidence: 99%